Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Make h the subject of the formula g = √h + i

Sagot :

Answer: h =(g-i)²

Step-by-step explanation: g=√h + i

Subtract I from both sides of the equation

g-i = √h+i-i

Simplifying,

g-i = √h

Take the square of both sides

(g-i)² = (√h)²

Simplifying, (g-i)² = h

Hence, h= (g-i)²

Hope it helps!